An Unusual Case of Transorbital Penetrating Brain Injury due to Fall on Branch of a Tree - Ramdurg, Shashank Ravindra; Hasa, Chandra; Maitra, Jayabrata (Indian Journal of Neurotrauma, 2015)
Penetrating injury of the skull and brain are relatively uncommon wounds, representing about 0.4% of all head injuries. The orbit is an easy path for low velocity foreign bodies into the cranium. Severity of the injury may be masked by superficial wounds and lack of a primary neurological deficit. Here, we present an unusual and a dramatic case wherein a patient was brought to the hospital with a branch of a tree penetrating into the left orbit. We also highlight the usage of 3D reconstruction computed tomography for nonradiopaque objects such as, wooden stick, thus, obviating the need for routine magnetic resonance imaging in these cases. The patient was successfully operated on at the institute and the patient had postoperatively preserved vision and eye movements.
Keywords: penetrating brain injury; transorbital; posttraumatic epilepsy